THU0454 OA Pain Phenotypes Associated with Structural Progression and Change in Pain Over Time in Two Phase III Clinical Studies with Symptomatic Knee OA. (9th June 2015) - Bihlet, A.R.; Bay-Jensen, A.-C.; Karsdal, M.A.; Byrjalsen, I.; Riis, B.J.; Christiansen, C.; Andersen, J.R.; Gühring, H.; Michaelis, M.; Ladel, C.
Abstract : Background: Osteoarthritis (OA) is recognized as a heterogeneous disorder, with several possible drivers of disease progression, including involvement of bone, cartilage and synovium. The degree of joint pain has been shown to be both diagnostic and prognostic for OA, but meaningful clinical characteristics to identify the group of patients at risk of rapid progression are still needed. Objectives: The aim of this analysis was to identify key pain characteristics (WOMAC 5 pain questions) associated with risk of structural progression, and notable changes in reported pain over time. Methods: A combined post-hoc analysis of two phase III RCTs (NCT00486434 and NCT00704847 ), evaluating the efficacy and safety of oral salmon calcitonin in patients with painful knee OA (N=2, 206) was performed. Analysis of structural progression was made based on data from the placebo group only, stratifying patients into quintiles of baseline (BL)-reported WOMAC pain level and further investigating the 5 WOMAC pain subscale questions: Q1; during walking on a flat surface, Q2; using stairs (up or down), Q3 at night while in bed, Q4; sitting or lying and Q5; while standing. The association between joint space narrowing (JSN) and WOMAC pain was assessed in a mixed model with JSN as dependent variable and other relevant BL variables as fixed effects. Results: Spearman correlation coefficients indicates that each WOMAC pain sub-score expresses individually different information, as rho coefficients ranged from a minimum of 0.40 between Q2 and Q3, and maximally 0.67 for Q3 and Q4 (p<0.0001 for both). The average observed change in the individual pain sub-scale levels indicated a heterogeneous development of pain characteristics over time, as the observed reduction in Q3 and Q4-pain was lower compared to other sub-scores. The relative change in overall WOMAC pain-score at year 2 was not significantly influenced by level of BL pain score. For each of the sub-score questions, a trend towards higher BL pain level being associated with higher relative and absolute pain relief was observed at year two, with some differences among the individual sub-score questions. Separate analysis of target and contralateral knees revealed interesting differences in association of BL pain level and structural progression. JSN of target knees appeared to be independent of BL levels of Q1-Q5, whereas in contra-lateral knees there was a tendency of higher BL levels of Q1, Q2 and Q5 being associated with higher JSN (Figure ). These results highlight differences in perceived pain caused by osteoarthritis over time, and may be indicative of individual pain phenotypical characteristics. The results indicate that acute, likely nociceptive, pain associated with walking and standing was more associated with structural progression than what may be interpreted as a possibly different, perhaps centrally augmented pain experienced without direct mechanical loading of the joint. Conclusions: These data from a large clinical trial dataset in OA describe significant associations between pain, pain subtypes and progression in OA, which may be related to different biochemical disease drivers. Acknowledgements: We wish to sincerely thank all the participants and investigators of the CSMC021C2301/02 studies. Disclosure of Interest: A. Bihlet: None declared, A.-C. Bay-Jensen Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, M. Karsdal Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, I. Byrjalsen Employee of: Nordic Bioscience, B. Riis Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, C. Christiansen Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, J. Andersen Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, H. Gühring Employee of: Merck Serono, M. Michaelis Employee of: Merck Serono, C. Ladel Employee of: Merck Serono